Hypoxia-inducible factor-2α activation promotes colorectal cancer progression by dysregulating iron homeostasis - Xue, Xiang (2012)
Hypoxia-inducible factor (HIF), a key modulator of the transcriptional response to hypoxia, is increased in colon cancer. However, the role of HIF in colon carcinogenesis in vivo remains unclear. In this study, we found that intestinal epithelium-specific disruption of the von Hippel-Lindau tumor suppressor protein (VHL) resulted in constitutive HIF signaling, and increased HIF expression augmented colon tumorigenesis in the Apc(min/+) intestinal tumor model. Intestine-specific disruption of Vhl increased colon tumor multiplicity and progression from adenomas to carcinomas. These effects were ameliorated in mice with double disruption of Vhl and HIF-2α. Activation of HIF signaling resulted in increased cell survival in normal colon tissue, however tumor apoptosis was not affected. Interestingly, a robust activation of cyclin D1 was observed in tumors of Apc(min/+) mice in which HIF-2α was activated in the intestine. Consistent with this result, BrdU incorporation indicated that cellular proliferation was increased in colon tumors following HIF activation. Further analysis demonstrated that dysregulation of the intestinal iron absorption transporter divalent metal transporter-1 (DMT-1) was a critical event in HIF-2α-mediated colon carcinogenesis. These data provide a mechanistic basis for the widely reported link between iron accumulation and colon cancer risk. Together, our findings demonstrate that a chronic increase in HIF-2α in the colon initiates pro-tumorigenic signaling which may have important implications in developing preventive and therapeutic strategies for colon cancer.